The Innovation JourneyThe Innovation Journey, by Van de VenAndrew PolleyDouglas E. GarudRaghu, and VenkataramanSankaran. New York: Oxford University Press, 1999. - Edmondson, Amy C. (Academy of Management Review, 2000)
The book “The Innovation Journey,” by Andrew Van de Ven, Douglas E. Polley, Raghu Garud and Sankaran Venkataraman, is a summary of the results of detailed longitudinal field research on fourteen innovations carried out by thirty researchers over 17 years. The book's almost 400 pages of text are densely packed with ideas, data, and conclusions. The helpful, if at times heavy-handed, structure used to organize all of this material makes the book accessible: its core messages are previewed, presented, and reviewed—perhaps consciously mimicking the iterative, cyclic innovation journey itself, as seen by the authors.